1989
DOI: 10.1111/j.1151-2916.1989.tb06116.x
|View full text |Cite
|
Sign up to set email alerts
|

Particle Orientation During Tape Casting in the Fabrication of Grain‐Oriented Bismuth Titanate

Abstract: Slurries containing platelike BiaTi3OI2 particles have been tape cast to prepare green sheets with aligned particles. The slurries contain well-dispersed particles and show nearly Newtonian flow behavior. The effect of slurry composition and casting conditions on the particle orientation has been examined. The particle orientation in the green sheet is determined mainly by powder content; other parameters, such as binder content, casting speed, and blade opening, have little effect. The interaction between par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
89
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 127 publications
(91 citation statements)
references
References 10 publications
2
89
0
Order By: Relevance
“…Several methods were examined to obtain textured ceramics. Hot-forging, templated grain growth (TGG) method and reactive TGG method were proposed [32,101,102], and highly h001i textured ceramics were obtained for several BLSFs of Bi 4 Ti 3 O 12 , NBT, and CBT [23,103,104]. It was reported that the electromechanical coupling coefficients and piezoelectric constants of highly textured BLSF ceramics were two or three times larger than those of randomly oriented ceramics.…”
Section: Ts1-mode Vibration Of Oriented Blsf Ceramicsmentioning
confidence: 99%
“…Several methods were examined to obtain textured ceramics. Hot-forging, templated grain growth (TGG) method and reactive TGG method were proposed [32,101,102], and highly h001i textured ceramics were obtained for several BLSFs of Bi 4 Ti 3 O 12 , NBT, and CBT [23,103,104]. It was reported that the electromechanical coupling coefficients and piezoelectric constants of highly textured BLSF ceramics were two or three times larger than those of randomly oriented ceramics.…”
Section: Ts1-mode Vibration Of Oriented Blsf Ceramicsmentioning
confidence: 99%
“…to form slurry which is tape-cast by a doctor-blade technique. The shear stresses acting on the slurry during casting align the platelike particles with their plate face parallel to the sheet surface [9,35]. The cast sheet is cut and laminated to form a green compact.…”
Section: Introductionmentioning
confidence: 99%
“…As-synthesized BLSF particles often exhibit platelike shapes with a well-developed c-face [7]. The c-face laminated texture can be easily produced with conventional fabrication techniques such as hot pressing and tape casting [4,[7][8][9][10]. However, a new method is needed to orient the c-axis normal to the lamination.…”
Section: Introductionmentioning
confidence: 99%